Trend of Having More Name Parts in Homogeneous Community - Ajar Pradika Ananta Tur (Universitas Ahmad Dahlan, 2022)
The intersection of loyalty to tradition among Prajurit Karaton and the demands of the times, particularly in terms of naming, is a topic that deserves to be researched. Furthermore, the community characteristics that are usually raised in scientific writings about naming are heterogeneous communities, so homogeneous communities become an important supporting component that completes the topic. This is a qualitative study that uses the Prajurit Karaton as the primary data source and a list of the names of their offspring as the secondary data. As a result, the names of the Prajurit Karaton’s offspring changed from mostly mononyms in the 1960s to polynyms in the 2010s. Nonetheless, the identity of a Javanese society remains. This also demonstrates that the Prajurit Karaton give names in accordance with the times while maintaining their identity as Javanese people and the Javanese cultural values.